2012
DOI: 10.1136/bcr-2012-007552
|View full text |Cite
|
Sign up to set email alerts
|

Transient cortical blindness as a manifestation of solitary cysticercus granuloma

Abstract: Neurocysticercosis is recognised as a significant cause of neurological morbidity in endemic regions. The wide range of pleomorphic and non-specific neurological manifestations of neurocysticercosis must be kept in mind by physicians, as the disease has shown resurgence in developed countries. When an atypical presentation of an unusual tropical disease occurs in non-endemic regions, the diagnosis is often missed. We describe a case of a 4-year-old girl who presented with a history of transient bilateral loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…31,32 Although this is theoretically possible-and must occur in a reduced percentage of cases-several pieces of evidence favor a causal relationship between NCC and recurrent nonprovoked seizures. Published evidence include abundant descriptions of cases with focal epilepsies related to the location of a single parasite in the brain parenchyma, [33][34][35][36][37] the higher prevalence of epilepsy in cysticercosis-endemic areas when compared with nonendemic regions, 38 and the occurrence of inflammatory changes surrounding parenchymal brain cysticerci immediately after a seizure in up to 50% cases. 39 In addition, although it has been suggested that some degenerating cysticerci may induce reactive seizures due to transient episodes of inflammation, calcified cysticerci-such as those Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Although this is theoretically possible-and must occur in a reduced percentage of cases-several pieces of evidence favor a causal relationship between NCC and recurrent nonprovoked seizures. Published evidence include abundant descriptions of cases with focal epilepsies related to the location of a single parasite in the brain parenchyma, [33][34][35][36][37] the higher prevalence of epilepsy in cysticercosis-endemic areas when compared with nonendemic regions, 38 and the occurrence of inflammatory changes surrounding parenchymal brain cysticerci immediately after a seizure in up to 50% cases. 39 In addition, although it has been suggested that some degenerating cysticerci may induce reactive seizures due to transient episodes of inflammation, calcified cysticerci-such as those Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Several population- [ 3 , 4 ] and clinic-based [ 8 - 10 ] studies have shown that primary headaches are more prevalent in subjects with neurocysticercosis. Neurocysticercosis with occipital lesions can even mimick migraine with visual aura [ 11 - 13 ], which was not the case in our patient.…”
Section: Discussionmentioning
confidence: 65%
“…2 Transient cortical blindness in a 4-year-old boy with underlying NCC has been described. 3 Being a treatable and preventable entity, it seems prudent to consider NCC in children from endemic regions who present with sudden onset neurological or cognitive disorders including unusual clinical manifestations such as amaurosis fugax. Additionally, neuroimaging is recommended in suspected cases of occipital epilepsies to rule out structural lesions such as NCC.…”
mentioning
confidence: 99%